Pentavalent Vaccine‐Induced Immune Thrombocytopenia: A Case Report From Nepal - Ramesh Khadayat; Sailesh Shrestha; Tilak Gautam; Sagar Rana Magar; Prashant Bhatta (Clinical Case Reports)
ABSTRACT Immune thrombocytopenia (ITP) is an autoimmune disorder marked by a low platelet count, leading to symptoms ranging from mild to severe bleeding. It can be triggered by various factors, including idiopathic origins, medications, malignancies, infections, and other autoimmune conditions. Though rare, ITP can also occur postvaccination. We report a case of a 3‐month‐old male who developed petechial rashes and mucosal bleeding following Pentavalent vaccination. This highlights the need for clinicians to recognize ITP as a potential complication of the Pentavalent vaccine. Educating parents about this rare but serious side effect is crucial.